The Influence of Supply Chain-Based Green Accounting (Scope 3 Emissions) on Company Sustainability Performance - Karunia Zuraidaning Tyas; Anastasia Anggarkusuma Arofah; Ummi Auliya Tusa'adah (International Journal Business and Entrepreneurship, 2026)
This research is motivated by the increasing demand for carbon emission transparency, particularly Scope 3 emissions, which reflect the environmental impacts of a company's entire supply chain, but are still not optimally disclosed in Indonesia. This study aims to analyze the effect of Scope 3 Emission Disclosure on Sustainability Performance, with Sustainable Supply Chain Performance as a mediator. This study uses a quantitative approach with an explanatory research type. Data were obtained from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange for the 2021–2024 period using a purposive sampling technique, resulting in 55 companies or 220 observations (firm-year). Data analysis was performed using the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method. The results show that Scope 3 Emission Disclosure has a positive and significant effect on Sustainable Supply Chain Performance and Sustainability Performance. In addition, Sustainable Supply Chain Performance also has a positive effect on Sustainability Performance and is able to mediate the relationship between Scope 3 Emission Disclosure and Sustainability Performance. These findings suggest that carbon emissions disclosure will be more effective in improving sustainability performance if accompanied by the implementation of sustainable supply chain practices. This research contributes to the development of supply chain-based green accounting and offers practical implications for companies in improving the quality of sustainability reporting and management